Spatial Distribution of Small and Big-Scale Modern Retail Through the Growth of Yogyakarta Urbanized Area - Ulfah Choerunnisa Nurul Litasari; Widiatmaka Widiatmaka; Khursatul Munibah; Machfud Machfud; Hefni Effendi (Faculty of Geography, Universitas Gadjah Mada, 2023)
The focus on the growth of modern retail has become increasingly important due to several generated externalities. Therefore, this research aimed to identify spatial distributional pattern of modern retail in order to implement precise policies. Data were obtained from The Department of Licensing Service of Yogyakarta City and supplemented with observation through Google Maps. The global pattern was analyzed using the Moran Index (Moran’s I), while the spatial pattern was evaluated using Local Indicators of Spatial Association (LISA). The analysis resulted in a significant cluster pattern for small and big-scale modern retail. The LISA analysis indicated the existence of agglomeration in the suburban area, which was the urban growth area with a high-high (HH) cluster of both small and big-scale modern retail in exact locations. In conclusion, agglomeration in the suburban area was of great concern for policymakers due to the possibility of conflicts.